Small bowel perforation with iliac artery prosthesis stump : a case report = Perforacija tankog crijeva bataljkom proteze ilijačne arterije : prikaz slučaja - Figl, Josip (Array, 2021)
Aim: In this case we report an unusual complication after retroperitoneal formation of an iliac artery prosthesis-stump – a bowel perforation and sepsis. Case report: During the open urology surgery a right external iliac artery was iatrogenic injured and iliofemoral bypass grafting was performed. Eight months thereafter, due to an inguinal site graft infection and graft occlusion, the distal part of the prosthesis was transacted and removed, and the proximal, retroperitoneal part, was closed and over sewn in the zone without any sign of infection present. This prosthesis-stump caused a very unusual complication – a small bowel perforation three months thereafter. Conclusion: The whole retroperitoneal graft should always be removed with no stump formation to avoid this complication.